Characterization of Langmuir Films Prepared from Copolyesterurethanes Based on Oligo(ω‐pentadecalactone) and Oligo(ε‐caprolactone) Segments. Issue 24 (13th October 2014) - Schöne, Anne‐Christin; Schulz, Burkhard; Richau, Klaus; Kratz, Karl; Lendlein, Andreas; Lendlein, Andreas; Behl, Marc
<x xml:space="preserve">Abstract</x> A series of multiblock copolymers (PDLCL) synthesized from oligo(ω‐pentadecalactone)diol (OPDL) and oligo(ε‐caprolactone)diol (OCL), which are linked by 2, 2(4), 4‐trimethyl‐hexamethylene diisocyanate (TMDI), is investigated by the Langmuir monolayer technique at the air–water interface. Brewster angle microscopy (BAM) and spectroscopic ellipsometry are employed to characterize the polymer film morphologies in situ. PDLCL containing ≥40 wt% OCL segments form homogeneous Langmuir monofilms after spreading. The film elasticity modulus decreases with increasing amounts of OPDL segments in the copolymer. In contrast, the OCL‐free polyesterurethane OPDL‐TMDI cannot be spread to monomolecular films on the water surface properly, and movable slabs are observed by BAM even at low surface pressures. The results of the in situ morphological characterization clearly show that essential information concerning the reliability of Langmuir monolayer degradation (LMD) experiments cannot be obtained from the evaluation of the π–A isotherms only. Consequently, in situ morphological characterization turns out to be indispensable for characterization of Langmuir layers before LMD experiments. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>